Pojęcie kultury między tradycją a współczesnością. Od perspektywy filozoficznej do edukacyjnej = The Notion of Culture between Tradition and Today. From Philosophical to Educational Perspective - Strouhal, Martin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The text deals with the problem of cultural relativism in the present-day school education. It describes two notions of culture, the classic and the relativist one as well as the classical and postmodern philosophy behind them. It depicts the situation in school education (humanities, art education) under the massive impact of sociologically influenced notion of culture.
Keywords: klasyczne pojęcie kultury; nauki społeczne; relatywizm kulturowy; edukacja szkolna; banalizacja edukacji; classical notion of culture; social sciences; cultural relativism; school education; banalization of education